What is the value of social prescribing? - Kimberlee, Richard (Advances in Social Sciences Research Journal, 2016)
General practice is in crisis. Across the UK different models of social prescribing have evolved to meet the growth in patient attendance. Although there is growing evidence of their efficacy there is little evidence of their value. Analysing one holistic social prescribing intervention this research adopts a social return on investment approach. Using an impact questionnaire, including validated items impact of the programme was assessed on 128 new patients over 12 months. This was followed up with semi-structured interviews with 40 patients; analysis of GP attendance data and the recording of other social outcomes. Data collected show statistically significant improvement in: Public Health Questionnaire 9 (p=<0.001), Generalized Anxiety Disorder 7 (p=<0.001), the Friendship Scale scores for social isolation (p=<0.001); the Office National Statistics’ Wellbeing measures (item range p=<0.05 to p=<0.001) and the International Physical Activity Questionnaire item for moderate exercise. There was a social return on investment of £2.90 for every £1 invested. Getting a broader perspective on value is vital to developing the business case to encourage commissioners to invest in social prescribing. Understanding and monetising broader social impact is vital to describing the full value of social prescribing.